Enhanced Cytotoxic Activity of Mitochondrial Mechanical Effectors in Human Lung Carcinoma H520 Cells: Pharmaceutical Implications for Cancer Therapy - González Rubio, Sergio; Montero Pastor, Nuria; García, Carolina; Almendro-Vedia, Víctor G.; Ferrer, Irene; Natale, Paolo; Paz-Ares, Luis; Lillo, M. Pilar; López-Montero, Iván (Frontiers in Oncology, 2018)
Cancer cell mitochondria represent an attractive target for oncological treatment as they have unique hallmarks that differ from their healthy counterparts, as the presence of a stronger membrane potential that can be exploited to specifically accumulate cytotoxic cationic molecules. Here, we explore the selective cytotoxic effect of 10-N-nonyl acridine orange (NAO) on human lung carcinoma H520 cells and compare them with healthy human lung primary fibroblasts. NAO is a lipophilic and positively charged molecule that promotes mitochondrial membrane adhesion that eventually leads to apoptosis when incubated at high micromolar concentration. We found an enhanced cytotoxicity of NAO in H520 cancer cells. By means Fluorescence lifetime imaging microscopy (FLIM) we also confirmed the formation of H-dimeric aggregates originating from opposing adjacent membranes that interfere with the mitochondrial membrane structure. Based on our results, we suggest the mitochondrial membrane as a potential target in cancer therapy to mechanically control the cell proliferation of cancer cells.